LUK 24:13-35 DAN TEOLOGI SINODALITAS - Bangun, Nathanio C. Maranatha; Marmidi, F.X.; Stanislaus, Surip (UNIKA Santo Thomas, 2024)
This study seeks to explore how the Gospel of Luke 24:13-35 embodies a theology of synodality. The theology of synodality has become a central focus in the life of the Catholic Church today, particularly since Pope Francis highlighted its importance in the third millennium. Synodality, etymologically meaning